Nightglow observations of OI 630 nm emission during the beginning of solar cycle 24 over 25°N, India - Parihar, Navin; Kakad, Bharati; Mukherjee, G.K. (My University, 2012)
This paper presents the first nightglow observations of the thermospheric red line emission of atomic oxygen at 630 nm from Allahabad (25.4°N, 81.9°E), a low-latitude station in India, during October-November 2009 and 2010. These observations were made using a CCD based All-Sky Imaging system. Most of the observations presented here represent geomagnetically quiet nights. The variability of OI 630 nm emission as observed from this station has been presented and discussed.
Keywords: Nightglow emission; Thermospheric red line emission